BSCI-02. tGLI1 IS A NOVEL, ACTIONABLE TARGET FOR THE TREATMENT OF BREAST CANCER BRAIN METASTASES. (12th August 2019) - Doheny, Daniel; Sirkisoon, Sherona; Rimkus, Tadas; Zhu, Dongqin; Aguayo, Noah; Harrison, Alexandria; Anguelov, Marlyn; Xing, Fei; Metheny-Barlow, Linda; Watabe, Kounosuke; Thomas, Alexandra; Masters, Adrianna Henson; et al.
Abstract: Despite improvements in early detection and intervention, breast cancer remains the second leading cause of cancer-related death in women and the second most common cancer to metastasize to the brain. Current standard of care options for breast cancer brain metastases (BCBM) include stereotactic radiosurgery, whole-brain radiotherapy, and surgical resection. Local and distant recurrences are common leading to significant morbidity; effective FDA-approved drugs for these patients remain a significant unmet need. Our laboratory discovered an alternative splice variant of glioma-associated oncogene homolog 1 (GLI1), termed truncated GLI1 (tGLI1) that is a tumor-specific gain-of-function transcription factor preferentially expressed in most BCBM samples and recurrent gliomas. Recent results established that tGLI1 promotes breast cancer stem cells (BrCSCs) and is associated with preferential metastasis to the brain and radioresistance, justifying tGLI1 as an ideal therapeutic target for BCBM patients. To identify tGLI1-targeting agents, we screened 1, 520 compounds across three commercial drug libraries and found ketoconazole, an FDA-approved azole antifungal and component of previously studied anti-neoplastic regimens, selectively killed tGLI1-expressing breast cancer cells with heightened efficacy against the CSC subpopulation in vitro . tGLI1 knockdown abolished the ability of ketoconazole to target BrCSCs, indicating that ketoconazole effect is dependent on tGLI1. Intracardiac mouse studies showed ketoconazole selectively inhibited circulating tGLI1-positive breast cancer cells from developing into brain metastases and suppressed the progression of existing brain metastases. Mass spectrometry demonstrated ketoconazole effectively penetrated the blood-brain barrier (BBB) and blood-tumor barrier (BTB). Mechanistic studies suggest that ketoconazole-dependent cell kill is, in part, mediated through disruption of the tGLI1-STAT3 interaction. Collectively, our preclinical results demonstrate that ketoconazole is an effective inhibitor of BrCSCs and brain metastasis of tGLI1-positive breast cancer. Based on these promising preclinical data, we opened a window-of-opportunity study in patients with BCBM and recurrent gliomas to determine if ketoconazole treatment alters tGLI1 signaling in humans (NCT03796273).